Applying Holt’s double exponential smoothing technique to predict HIV prevalence among individuals aged 15-49 years for Burkina Faso (Texas Journal of Medical Science, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Burkina Faso from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s double exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue to decline over the out of sample period. Therefore, we encourage authorities to improve HIV case detection among the communities and strengthen preventive measures recommended by WHO.